1989
DOI: 10.1164/ajrccm/140.4.1033
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Abnormalities in Patients with Respiratory Failure after Multiple Trauma

Abstract: We present a prospective study, designed to evaluate surfactant abnormalities in severely injured patients during the course of post-traumatic pulmonary dysfunction. Serially obtained bronchoalveolar lavage fluids from noncontused lung areas (in total, 132 samples from 17 patients) were analyzed for alveolar phospholipid composition and surfactant function in vitro during the first 14 days after trauma. The data were compared with those of 29 lavage samples obtained from 10 healthy control subjects and correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
101
1
6

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(115 citation statements)
references
References 19 publications
7
101
1
6
Order By: Relevance
“…In their first study, they examined BAL samples from trauma patients with respiratory failure (35). Unlike our study, they found that total lavage phospholipid content was not different than that of healthy control subjects.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In their first study, they examined BAL samples from trauma patients with respiratory failure (35). Unlike our study, they found that total lavage phospholipid content was not different than that of healthy control subjects.…”
Section: Discussioncontrasting
confidence: 64%
“…Pison and his colleagues have reported two recent studies of surfactant composition and functional activity in ARDS patients (35,36). In their first study, they examined BAL samples from trauma patients with respiratory failure (35).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, hydrolysis of PG occurs as early as 1 h after sPLA 2 -IIA administration, indicating that this enzyme could account for surfactant abnormalities observed at early phases in ARDS (17). In fact, alterations in the relative composition of the surfactant phospholipids are seen in patients with ARDS (17,18,43,44). A decrease in PG levels (by Ͼ80% in three of these studies) and a moderate reduction of PC levels were observed.…”
Section: Discussionmentioning
confidence: 75%
“…Наряду со снижением содержания основных классов ФЛ на блюдается относительное увеличение содержания минорных компонентов ФЛ, ненасыщенных ЖК в составе ФЛ [8,[90][91][92]. Обнаружено также уменьшение содержания САБ: SP А, SP В и SP С, но не SP D [8, 91 93].…”
Section: нарушения состава и свойств легочного сурфактанта при различunclassified
“…[94]. Несмотря на то, что вклад от дельных компонентов ЛС в защитные механизмы легочного по вреждения до конца не ясен, полагают, что существенное сниже ние содержания SP А [8,90,92,93], деградация SP А в легочной ткани [107] и уменьшение его опсонизирующей способности по отношению к различным патогенам вносят существенный вклад в снижение резистентности больных к гнойно септическим ос ложнениям ОРДС и ИВЛ [92,108].…”
Section: нарушения состава и свойств легочного сурфактанта при различunclassified